Intentional replantation: case report of an alternative treatment for endodontic therapy failure - Flares BARATTO FILHO; José Roberto VANNI; Orlando LIMONGI; Luiz Fernando FARINIUK; Rosana TRAVASSOS; Diana Santana ALBUQUERQUE (Revista Sul-Brasileira de Odontologia, 2005)
The aim of this study was to present an alternative treatment after the occurrence of endodontic therapy failure. The authors report a clinical case of a second maxillary permanent molar, which was indicated for intentional replantation as an alternative treatment. Extraction was performed followed by apicoectomy of the three roots and radicular decontamination with citric acid (pH=1) for 1 min; the roots were then retro-obturated with amalgam and the tooth replanted in the alveolus. The extra-buccal period lasted 15 min. Clinico-radiographical follow-up examinations were done at 2, 3 and 5 years and no symptoms or radicular resorption were found. There was bone neo-formation at the palatal root that had presented a periapical lesion. Intentional replantation can be indicated correctly as an alternative treatment for cases in which conservative endodontic therapy or surgical technique cannot be performed.